Native and exotic fishes in a Patagonian reservoir with rainbow trout cage culture: spatial and trophic resource use - Nabaes Jodar, Diego Nicolás (2017)
Although the interactions of exotic salmonids with native Patagonian fishes are well known, little is known about the ecology and impact of farmed fish escapees. Salmonid production in Argentina is largely concentrated in the Alicurá reservoir in north Patagonia, where fish community studies have been scarce. Here, we assess and compare the spatial distribution, body size-condition and diet of the different fish species in this reservoir. Strong vertical segregation was observed between exotic rainbow trout Oncorhynchus mykiss (both escapees and wild), dominating the littoral zone, and native Percichthys trucha which dominate the medium and deep strata. Low piscivory-benthivory and high zooplanktivory were observed for rainbow trout, which are regionally rare. Escaped farmed rainbow trout (ERT) diet included abundant indigestible items along with wild prey. Higher body condition of P. trucha close to farms, as well as the regionally unprecedented high incidence of Daphnia sp. in the guts of all the species suggest that farm nutrient discharges have had significant impacts. Finally, the high body condition of ERT, together with their wild food diet and the long distance dispersal observed, demonstrate post-escape success, drawing our attention to potential upstream dispersion affecting the biodiversity and fisheries of Patagonian rivers and lakes.